2013
DOI: 10.1177/1060028013504740
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Allopurinol in Chronic Kidney Disease

Abstract: Studies evaluating allopurinol use in patients with CKD have reported inconsistent findings relative to safety and efficacy. Providers should be aware of the potential risk of allopurinol hypersensitivity syndrome as well as the need for reducing the initiation dose and gradual titration of allopurinol to safely achieve a target serum urate level in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
0
23
1
2
Order By: Relevance
“…23 Later studies have contradicted this notion. 24 However, it is recommended to begin with a low dose as recent work has shown that higher starting doses of allopurinol may increase the risk of allopurinol hypersensitivity syndrome. 25 The response to therapy has generally been monitored by assessment of 2,8-DHA crystals in the urine sediment, which may not be accurate enough to guide drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…23 Later studies have contradicted this notion. 24 However, it is recommended to begin with a low dose as recent work has shown that higher starting doses of allopurinol may increase the risk of allopurinol hypersensitivity syndrome. 25 The response to therapy has generally been monitored by assessment of 2,8-DHA crystals in the urine sediment, which may not be accurate enough to guide drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the harmful side effect/adverse reaction profile of these medications contributes to better awareness and knowledge. A recent review of the safety and efficacy of allopurinol in CKD suggests that incidence of allopurinol hypersensitivity syndrome and other adverse effects like Stevens-Johnson syndrome can occur with a higher frequency in patients with impaired renal function [53]. Similarly, colchicine toxicity is more common among those with renal impairment and can be fatal [5456].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review study reported by Thurston et al [35] discussed efficacy and safety of allopurinol in patients with CKD. The authors reported that, some trials have demonstrated an increased risk of allopurinol-induced adverse reactions in patients with CKD, whereas others have not confirmed renal insufficiency as a risk factor.…”
Section: Dose Adjustment and Safety Of Allopurinol In Patients With Ckdmentioning
confidence: 99%
“…The authors reported that, some trials have demonstrated an increased risk of allopurinol-induced adverse reactions in patients with CKD, whereas others have not confirmed renal insufficiency as a risk factor. More CKD patients achieved a target uric acid level in studies where the allopurinol dose was titrated to effect as compared with those studies in which patients were given renally adjusted or untitrated allopurinol doses [35]. …”
Section: Dose Adjustment and Safety Of Allopurinol In Patients With Ckdmentioning
confidence: 99%